Explotación de recursos en la cordillera Huayhuash: la minería y el turismo - Robles Mendoza, Román (2006)
The national reserve of the Huayhuash mountain range, located in the borders of the departments of Ancash, Lima and Huánuco, has become in the last years a center coveted for the exploitation of natural resources. Landscaping kindness of high snow-covered mountains, lagoons, plains and defiles have turned it one of the tourist routes of high value in the country and the varied wealth of mineral reserves of good law in the subsoil of this mountain range has caused the foreign investment for its operation. In this article we give account on the dynamics of the actors, in its intentions of exploitation of the natural resources, facing conflicts of interests and making effort to obtain the agreement of the parts for a rational advantage of these wealth.